Іноетнічні запозичення та їх вплив на формування одягу українських міщан (За матеріалами XIV-XVI століть) - Косміна, О. (Народна творчість та етнографія, 2005)
The analysis of historical sources XIV - XVI centuries has found out wide use of the goods of foreign manufacture (the fabrics, various kinds of clothes, costume jewellery) for formation of clothes of inhabitants of the Ukrainian cities. Foreign terms in due course have started to be realized as own. This historical period became a basis for the further formation of regional types of national clothes.